Morphometric Study Of Human Placenta In Preeclampsia Associated With Intrauterine Growth Retardation - G.PRIYA,; K.BHAVINA,; S.SUNDARAPANDIAN, (International Journal of Pharma and Bio Sciences, 2012)
The placenta is the special pregnancy organ that links a mother to the child for the transport of fetal nutrition through umbilical cord. Preeclampsia is a major disorder of pregnancy which mainly originates in the placenta and is associated with retarded fetal and placental growth. The aim of this study was to compare the morphometric measures of placenta in pregnancies complicated by Preeclampsia (PE) associated with Intrauterine Growth Retardation (IUGR), with that of normal. Totally 180 placentas were studied. Out of which 80 placentas from PE+IUGR and 100 of normal. There was a significant reduction in Placental weight,Diameter, Volume,Thickness, Birth weight of baby,Foeto-placental ratio, Number of cotyledons, Length of the umbilical cord, Gestational week in PE with IUGR compared to normal. These Morphometric changes might cause placental insufficiency in preeclampsia which results in IUGR.